Development of emulsion gel as fat replacer in chicken meat emulsion for the production of reduced-fat meat products - Abu Bakar, Asyrul Izhar (2024)
In recent years, reduced-fat meat products have surged in popularity as they are healthier compared to meat products with animal fats. Animal fat gives good quality characteristics to meat products but it is associated with noncommunicable diseases. Structured oils made from emulsion gels have garnered interest in replacing animal fat. Thus, this study consisted of four objectives, which generally aimed to produce reduced-fat chicken products for different meat rigor conditions with developed emulsion gels as fat replacers. In the first objective, different types of animal fats such as chicken skin, beef fats and lamb fats were compared in terms of physicochemical, molecular and microstructural characteristics. The fatty acid compositions of chicken skin, beef and lamb fats ranging from 55.43 to 72.02% for saturated fatty acids. Xray diffraction (XRD) showed that chicken skin crystallised in a beta prime (β') polymorph while lamb and beef fat crystallised in an alpha (α) polymorph. Microscopic images showed that lamb and beef fats had a larger and more heterogeneous structure compared to chicken skin which was evenly distributed. For the second objective, three systems were studied: emulsion gel A (EGA) and emulsion gel B (EGB), which promoted electrostatic interaction, and emulsion gel C (EGC), which did not. Smaller particle size (p<0.05) in EGA and EGB increased gel strength, hardness and oxidative stability. Smaller droplets would result in a better-aggregated network of threedimensional structures which leads to better physicochemical properties of the emulsion gels. Electrostatic protein-polysaccharide interactions were most enhanced by EGA, making it suitable for use for the third objective. Following this, the chicken meat emulsion properties of pre- and post-rigor using chicken skin and EGA as a fat replacer were determined. The findings showed that the EGA-replaced chicken emulsion had higher moisture and lower fat (p<0.05). EGA also reduced saturated fat in chicken emulsion from 68% to 34%. EGAreplaced chicken emulsion had the smoothest surface regardless of rigor states, thus, indicating that the meat emulsion was well emulsified. The fourth objective indicated chicken sausage combined with EGA had a considerably (p<0.05) decreased fat content. This work established that the water holding capacity (WHC) of the chicken sausage with emulsion gel could mimic the WHC of chicken sausage with animal fat. This could be attributed to the presence of hydrocolloids present in the emulsion gel which could bind to water. Sensory analysis showed that panellists did not detect any significant differences (p>0.05) between the chicken sausage samples. Conclusively, the current study successfully demonstrated that the incorporation of EGA as fat replacers in chicken emulsion and sausage reduced fat content compared to the control sample while maintaining quality regardless of rigor conditions. This study ascertained that the meat products developed could serve as a valuable resource for researchers and also contribute to the development of healthier meat products. Thus, it can be concluded that emulsion gel has the potential as a fat replacer in the production of reduced-fat meat products.